2021
DOI: 10.1051/e3sconf/202127309005
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of the provision of additional hotel services as a factor in the development of business tourism in the city of Rostov-on-Don

Abstract: This study is aimed at analyzing the peculiarities of the functioning of the hotel services market in the city of Rostov-on-Don and the Rostov region and identifying the specifics of providing additional hotel services by hospitality industry enterprises positioning themselves as congress hotels, hotels offering conference services. The article evaluates the total number of rooms for accommodation in the city of Rostov-on-Don of a business nature and the range of additional hotel services provided by them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…When identifying the specifics of innovations in the additional education of workers in the service sector, it was necessary to analyze the works of such authors as: L. N. Kazmina, V. V. Provotorina (2015, 2016) [12,13], L. Kazmina, V. Makarenko, V. Provotorina, E. Shevchenko (2020) [14], L. Kazmina, V. Provotorina, V. Makarenko, A. Petrenko (2020) [15], L. N. Kazmina, V. S. Makarenko, V. V. Provotorina, T. N. Grigorenko [16]. Jianwei Qian, Rob Law, Xinjian Li (2019) [17], Petrenko, A., Ekinil, G., Provotorina, V. [18], L. N. Kazmina, V. V. Provotorina, I. M. Komarnitsky (2022) [19].…”
Section: Methodsmentioning
confidence: 99%
“…When identifying the specifics of innovations in the additional education of workers in the service sector, it was necessary to analyze the works of such authors as: L. N. Kazmina, V. V. Provotorina (2015, 2016) [12,13], L. Kazmina, V. Makarenko, V. Provotorina, E. Shevchenko (2020) [14], L. Kazmina, V. Provotorina, V. Makarenko, A. Petrenko (2020) [15], L. N. Kazmina, V. S. Makarenko, V. V. Provotorina, T. N. Grigorenko [16]. Jianwei Qian, Rob Law, Xinjian Li (2019) [17], Petrenko, A., Ekinil, G., Provotorina, V. [18], L. N. Kazmina, V. V. Provotorina, I. M. Komarnitsky (2022) [19].…”
Section: Methodsmentioning
confidence: 99%
“…Trends and specifics of development of the hotel business both in Russia and abroad are a subject matter of papers of such authors as: Mehmet Ali Köseoglu, Mehmet Altin Eric Chan, Omer Faruk Aladag, 2020 [1], A. Oukil. N. Channouf, Channouf Asma Al-Zaidi, 2016 [2], L. N. Kazmina, V. S. Makarenko, V. V. Provotorina, T. N. Grigorenko, A. S. Petrenko, G. E. Ekinil, E. M. Shevchenko [3][4][5][6][7][8][9][10].…”
Section: Background and Methodsmentioning
confidence: 99%
“…In the relevant literature, it is observed that bleisure tourism is generally examined conceptually due to being a new concept (Lichy & Mcleay, 2018;Kasalak et al, 2019;Alp & Yazıcı Ayyıldız, 2020;Pinho & Marques, 2021;Raykova, 2021;Walia et al, 2021;Вагапова, 2023), Mercan & Sandıkcı, 2024). On the other hand, research has been made on bleisure tourism and bleisure tourists, generally associated with variables such as perceived quality and intention to revisit (Ünal & Özgürel, 2021), competitive development in health tourism (Keadplang, 2018), competitiveness (Caicedo-Barreth et al, 2020), experience chain and destination marketing (Chung et al, 2020), sustainable development (Petrenko et al, 2023). Regarding motivational factors, besides a systematic literature review (Sohaili et al, 2022), two studies targeting business people and human research managers have been encountered (Sardest & Ivanauskas, 2019;Çetinöz & Hazarhun, 2020).…”
Section: Introductionmentioning
confidence: 99%